Treinamento de habilidades sociais em grupo com professores de crianças com dificuldades de aprendizagem: uma análise sobre procedimentos e efeitos da intervenção. - Vila, Edmarcia Manfredin (Universidade Federal de São Carlos, 2005)
Social Skills Training (SST) can be used to increase teachers social competence, contributing to the development of interactive contexts in the classroom as well as to the student s learning. The purpose of this research was to elaborate and describe intervention procedures used in a group SST program with teachers who work with children that present learning difficulties, consisting of 15 sessions for the development of social skills. The effects of the SST were analysed in terms of: a) acquisition of social skills classes and b) generalization of social skills learned in the sessions for the classroom context. The sample included 10 teachers, in the 26-54 age range. The data gathering procedure involved the use of the Interpersonal Relations Questionnaire (IRQ) before the intervention, the Social Skills Inventory (SSI) and the filming of each teacher with his/her students, before and after the intervention. The IRQ data showed that at the beginning the teachers had some difficulties in dealing with interpersonal conflicts in the classroom, demonstrating lack of social skills. It was also observed a certain incoherence in the verbal report related to some questions, highlighting flaws in the self-observation and self-knowledge repertoire. Based on the survey of the behavioral classes presented by the facilitator by means of the tape transcriptions, it was possible to classify the intervention procedures that had the following purposes: a) to investigate interpersonal difficulties; b) to analyse previous-consequent relations; c) to train specific social skills; d) presentation of positive results and; e) to sound out generalization which contributed to the learning of social skills and generalization for the classroom context. The SSI data showed that after the intervention there was an increase in the scores average of the group of teachers in all the social skills classes that were assessed. In the individual analysis some teachers showed much bigger changes than others and for some of them there was a slight decrease in the scores. As for the filming data in the classroom, there was no increase in all the social skills that were assessed, but in those that increased, the generalization was evidenced. The results obtained allow us to state that the improvement of the teachers social skills repertoire enables them to foster interactive contexts in the classroom, contributing to the student s academic and interpersonal development.
Social Skills Training with a group of teachers who deal with children with learning difficulties: An analysis on procedures and effects of the intervention.
Keywords: Capacitação de professores; Professores - formação; Interação professor - aluno; Dificuldades de aprendizagem; Habilidades sociais - avaliação e intervenção; Social Skills Training; Teacher-student interaction; Teacher s qualification; Learning and generalization difficulties; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL